Prototype Worlds and Characters In Selected Science Fiction: Exploring Science Fiction Worlds and Characters (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paperexamines prototype worlds and characters in selected Science Fiction (SF)texts. It utilises  certain principles ofI.A Richard‟sPractical Criticism, particularly in relation to “sense” and  “intention”, as the analytical framework. Itis found that the analysis of the worlds and characters reveals the authors‟ intention i.e. his aim, conscious or unconscious, andthe effect that is promoted to the readers. The words used by the authors to describe the SF worlds andcharacters have a task to perform  andthat is to convey meaning to readers so that they can make sense of what isbeing communicated. This approach, although described as outdated by some, isuseful especially for higher education students who are studying this genre forthe first time. The texts included in the analysis are China Mieville‟s novel Perdido Street Station, Ted Chiang‟s novella “Liking What You See: A Documentary”  as well as two short stories - Mike Resnick‟s “The Elephants on Neptune” and Michael Swanwick‟s “The Dead”.